2012
DOI: 10.1007/s00586-012-2379-8
|View full text |Cite
|
Sign up to set email alerts
|

H3S2 (3 hooks, 2 screws) construct: a simple growing rod technique for early onset scoliosis

Abstract: Purpose The purpose of this study was to review the preliminary results of an original fusionless method of treatment for progressive scoliosis in young children. Methods This study retrospectively reviewed the clinical records and radiographs of 23 children with progressive scoliosis who failed to respond to conservative treatment and underwent fusionless surgery using a single solid growing rod construct. All of them were ambulatory and had a followup of minimum 2 years. Sixteen patients were treated by cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Curve correction after use of initial posterior release (with six also having anterior release) and internal distraction, and before definitive fusion averaged 53 % (from 104°to 49°); correction was 6 % after the second distraction procedure; and the mean final curve correction was 80 % (from 104°to 20°). We should also note the correction of the scoliotic curve can be obtained progressively by iterative lengthening the growing rod to treat evolutive scoliosis in young children [57][58][59][60][61]. Miladi et al [57] showed the average improvement in Cobb angle after each rod-lengthening of the growing rod was 12.9, which includes two parts, the loss of correction due to spine growth between two rod lengthenings (10°) and the improvement of correction (2.9°).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Curve correction after use of initial posterior release (with six also having anterior release) and internal distraction, and before definitive fusion averaged 53 % (from 104°to 49°); correction was 6 % after the second distraction procedure; and the mean final curve correction was 80 % (from 104°to 20°). We should also note the correction of the scoliotic curve can be obtained progressively by iterative lengthening the growing rod to treat evolutive scoliosis in young children [57][58][59][60][61]. Miladi et al [57] showed the average improvement in Cobb angle after each rod-lengthening of the growing rod was 12.9, which includes two parts, the loss of correction due to spine growth between two rod lengthenings (10°) and the improvement of correction (2.9°).…”
Section: Discussionmentioning
confidence: 97%
“…We should also note the correction of the scoliotic curve can be obtained progressively by iterative lengthening the growing rod to treat evolutive scoliosis in young children [57][58][59][60][61]. Miladi et al [57] showed the average improvement in Cobb angle after each rod-lengthening of the growing rod was 12.9, which includes two parts, the loss of correction due to spine growth between two rod lengthenings (10°) and the improvement of correction (2.9°). Moreover, the main scoliotic curve was corrected from 68°± 32°(range 31°-142°) before surgery and preoperative reduction to 33°( range 11°-71°) after surgery, and 29°(range 15°-63°) on average at the last follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…The proximal fixation comprises 3 hooks (2 supralaminar and 1 pedicular) and distal fixation is provided by 2 pedicular screws, in what is known as H3S2 assembly [18,19]. The rod, in concave or in $ position, is curved according to the target spinal profile.…”
Section: Single-rod Assemblymentioning
confidence: 99%
“…The conventional rod arm of the case-matched study [ 19 ] included by the sponsor was also included within the evidence base, totalling 16 studies. Of the 16 conventional rod studies, 15 were retrospective case series and the remaining one was a prospective case series [ 28 ].
Fig.
…”
Section: Review Of Clinical and Economic Evidencementioning
confidence: 99%